Organization of Full-Scale Analyses of Filtration-Thermal Regime of Tailings Dams on Permafrost Foundations (Organizatsiya Naturnykh Issledovaniy Filtratsionnotermicheskogo Rezhima Damb Khvostokhranilishch na Vechnomerzlykh Osnovaniyakh) - Sheynfeldt,G M (1977)
The planning and operation of tailings dump dams under arctic conditions have been carried out until the present time without standard documents or recommendations that consider the specific features of the climatic and permafrost conditions. This report presents an analysis of several tailings dump dams located in severe climates as well as a discussion of the use of piezometers. The conclusions presented substantially justifies calculation-theoretical forecasting of the formation of the temperature mode of the tailings sediment and dam foundation. (Author) Trans. of unidentified Russian report p116-131.